İran-Irak Savaşı: Türkiye Sınırlarında Terörizme Etkisi - Seçil ÖZDEMİR (Gazi Akademik Bakış)
In 1980, war began between Iran and Iraq which would last eight years and have effects continuing into the 21st cenutry. Turkey was affected by the war between its border neighbours and its outcomes from many aspects. During the war, terrorism developed on the east and southeast borders of Turkey. Turkey was surrounded by a terrorism problem with regional effect. The process of war provided infrastructure for the formation of this situation. The PKK (Partiyi Kargeranı Kürdistan) terror organization founded in 1979 began attacks targeting the Turkish Armed Forces in 1984. In this process, the PKK found opportunities to develop in camps founded along the Iran-Iraq-Syria borders neighbouring Turkey and in Lebanon, and succeeded in infiltrating the Turkish border in the problematic process created by conditions of war. After the IranIraq war ended, this threat to Turkey’s security was not removed. As a result, a war that Turkey was not included in created a long-term threat, not just from diplomatic, social and economical aspects, but with the terrorism problem developing on the borders In this study, within the basic framework of the Iran-Iraq War, the attitude of Turkey toward the warring parties during the war and the effects of the war on the emplacement of terrorism on the borders of Turkey will be assessed. Turkish media during this period, western media sources, diplomatic documents, and archive records were examined in the study. In addition, the statements of politicians of the period and memorial monuments were used for content analysis in the study. Furthermore, studies in the literature were used to improve the study.